Strengthening of the steel 20X of the binding of wedge columns by electrolyte-plasma hardening - Kombaev, К.К.; Ahmadiev, Р.Б.; Kassenova, А.Б.; Elemanov, Д.С.; Toktarbaeva, Г.М.; Sypainova, Г.С. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The global demand for oil and gas products has caused noticeable qualitative and quantitative changes in the applied technological processes for manufacturing parts and equipment for the extraction and transportation of petroleum products. Kazakhstan is the largest oil-producing country in the world, so the development of advanced technology to produce oil and gas equipment can stimulate industrial and economic growth. Traditional technologies for hardening critical parts of wedge string piping (WSP) are energy-intensive and labor-intensive, although they are used in many industrial enterprises. For the scientific study of the chemical-thermal hardening of a low-carbon alloyed slab, there was developed an experimental installation for electrolytic-plasma hardening made of steel 20X, GOST 33260-2015 (207 Steel), tying the wedge columns, an. Experimental studies of electrolytic-plasma hardening were carried out in various processing modes. The article describes dependence of the current-voltage characteristic of high-speed heating of a part on the temperature of the ionized electrolyte plasma. The article highlights the heat transfer processes of heating and hardening in the electrolyte by a mathematical model, and a regression formula. The article describes the main parameters of electrolytic-plasma hardening, and optimal processing modes. Raster elemental analysis indicates surface modification of the hardened layer of low-carbon alloy steel by carbon. The method of electrolytic-plasma hardening makes it possible to locally harden the mating working surfaces of the WSP die. The article investigates results of changing the microstructure and increasing the hardness relative to the initial state.